2012
DOI: 10.1245/s10434-012-2477-1
|View full text |Cite
|
Sign up to set email alerts
|

National Practice Patterns in Preoperative and Postoperative Antibiotic Prophylaxis in Breast Procedures Requiring Drains: Survey of the American Society of Breast Surgeons

Abstract: Background The aim of this study was to assess national practice patterns regarding use of perioperative antibiotics by surgeons performing breast operations requiring drainage tubes. Methods The members of the American Society of Breast Surgeons (ASBrS) were surveyed regarding use of perioperative antibiotics for breast operations requiring drains, with or without immediate tissue expander or implant reconstruction. Results Of 2857 ASBrS members contacted, 917 (32%) responded and all self-identified as su… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

1
35
0

Year Published

2014
2014
2023
2023

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 35 publications
(36 citation statements)
references
References 16 publications
1
35
0
Order By: Relevance
“…1). Articles investigating different instruments/surgical techniques [25,26,27], postsurgical physiotherapy [28], or breast infections without relation to the insertion of drains [29,30] were excluded. This left the 3 articles from Taylor et al [5], Andeweg et al [31], and Garbay et al [32].…”
Section: Resultsmentioning
confidence: 99%
“…1). Articles investigating different instruments/surgical techniques [25,26,27], postsurgical physiotherapy [28], or breast infections without relation to the insertion of drains [29,30] were excluded. This left the 3 articles from Taylor et al [5], Andeweg et al [31], and Garbay et al [32].…”
Section: Resultsmentioning
confidence: 99%
“…The present work describes a prospectively collected single-center case series evaluation and shows that, when based on clinical definition, late breast implant infection after [3,6,9,10]. A subsequent epidemiological definition suggested in order to avoid underreporting, to extend the ''early'' period up to 1 y after surgery thus encompassing distinct clinical stages in the case of breast reconstruction.…”
Section: Discussionmentioning
confidence: 96%
“…There is, however, still controversy in the breast reconstruction area on the definition of infection and on the observation time required to define actual implant infection. Indeed, in this regard, early reports studied implant infection using a limited time of observation more useful for surgical site infection (SSI) evaluation [3,9,10] and not for prostetic infection.…”
mentioning
confidence: 99%
See 1 more Smart Citation
“…In a survey of the members of the American Society of Breast Surgeons regarding the use of perioperative antibiotics for breast operations requiring drains, respondents continued antibiotic prophylaxis for 2 -7 days or until all drains were removed (38% and 39%, respectively) in cases without reconstruction, while in reconstruction cases 33% of respondents continued antibiotic prophylaxis for 2 -7 days or until all drains were removed (63). A similar study surveying the American and Canadian societies of plastic surgeons regarding drain use and perioperative antibiotic prophylaxis in cases of breast reconstruction found that 72% of plastic surgeons prescribed postoperative outpatient antibiotics in reconstruction patients with drains, with 46% continuing antibiotics until drains were removed (64).…”
Section: Resultsmentioning
confidence: 99%